The Association between Hypothermia during Emergency Room Admission and Newborn Mortality at Dr. Moewardi Hospital - Hidayah, Dwi; Rohsiswatmo, Rinawati; Hafidh, Yulidar (Journal of Maternal and Child Health, 2023)
Background: Hypothermia in newborns continues to be a significant issue and a leading cause of morbidity and mortality. The incidence of hypothermia in referral newborns is still high during hospital admission. Subjects and Method: This is a prospective cohort study conducted at Dr. Moewardi Hospital. Data collection was carried out on January 1, 2015, until March 31, 2015, for referred newborns. The dependent variable was mortality and the independent variables included gestational age, birth weight, sepsis, severe respiratory distress, and temperature at the time of admission at the ER. The chi-square test and logistic regression were used to analyze the data, with a cut-off value of p<0.05 cut off and a confidence interval of 95%. Results: There were 56 newborn referrals, with 60.7% incidence of hypothermia and 19.6% incidence with mortality. From the chi-square analysis, the variable of gestational age and weight did not meet the requirements of multivariate analysis (p> 0.25). The multivariate logistic regression analysis revealed a non-significant association between severe respiratory distress and mortality in referred newborns (OR= 5.25; 95% CI= 0.89 to 30.82; p= 0.066). After performing multivariate logistic regression analysis to obtain controlled ORs, there was a significant relationship between newborn referrals mortality and temperature at the time of ER admission (OR= 8.75; 95% CI= 1.07 to 3.26; p= 0.047) and sepsis (OR= 6.25; 95% CI= 150 to 28.69; p= 0.012) with mortality of referred newborns. Conclusion: The incidence of hypothermic referred newborns is high. Hypothermia during admission at the ER and sepsis are both associated with increased mortality in referred newborns. Keywords: newborns, hypothermia, mortality. Correspondence:Dwi Hidayah. Department of Child Health, Faculty of Medicine, Sebelas Maret University and Dr. Moewardi General Hospital, Jalan Kolonel Sutarto No.132, Surakarta 57126, Indonesia. Mobile: 08122623728 Email: dwihidayah_dr2020@staff.uns.ac.id